2005
DOI: 10.1073/pnas.0500755102
|View full text |Cite
|
Sign up to set email alerts
|

Robust in vitro activity of RebF and RebH, a two-component reductase/halogenase, generating 7-chlorotryptophan during rebeccamycin biosynthesis

Abstract: The indolocarbazole antitumor agent rebeccamycin is modified by chlorine atoms on each of two indole moieties of the aglycone scaffold. These halogens are incorporated during the initial step of its biosynthesis from conversion of L-Trp to 7-chlorotryptophan. Two genes in the biosynthetic cluster, rebF and rebH, are predicted to encode the flavin reductase and halogenase components of an FADH 2-dependent halogenase, a class of enzymes involved in the biosynthesis of numerous halogenated natural products. Here,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

8
278
0
10

Year Published

2005
2005
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 253 publications
(298 citation statements)
references
References 51 publications
8
278
0
10
Order By: Relevance
“…Recent work within the Walsh group has established that RebF and RebH act as a two-component reductase/ halogenase system (13). RebF is able to generate FADH 2 , and RebH uses this reduced flavin, along with O 2 and chloride ion, to generate an oxidizing halogen equivalent.…”
mentioning
confidence: 99%
“…Recent work within the Walsh group has established that RebF and RebH act as a two-component reductase/ halogenase system (13). RebF is able to generate FADH 2 , and RebH uses this reduced flavin, along with O 2 and chloride ion, to generate an oxidizing halogen equivalent.…”
mentioning
confidence: 99%
“…The kinetic parameters for RadH with selected substrates were determined (Table 1 and Figures S4–S10). Notably, the k cat values for RadH with iso‐quinoline 6 and coumarin 8 were significantly higher than those reported for Trp‐Hal enzymes with the natural substrate 3a, 13. Whilst kinetic analysis shows that monocillin II ( 1 ) is turned over more slowly than the other substrates, k cat / K m was not determined for 1 since saturation of the Michaelis–Menten curve was not attained.…”
mentioning
confidence: 78%
“…Substituted naphthalenes were also viable substrates, and monochlorinated compounds 10 and 11 were isolated in high yields. While these latter substrates were halogenated at their most activated sites, they nonetheless illustrate the ability of RebH to accept substrates significantly different from tryptophan.To further demonstrate the synthetic utility of RebH, we confirmed that the bromination capabilities of this enzyme [13] could be translated to the preparative scale, and addition of NaBr to the reaction medium provided 7-bromotryptophan (12) in 85% isolated yield. The reaction scale was also increased to enable chlorination of 100 mg of tryptophan using crude cell lysate, rather than purified enzyme, as a catalyst (Scheme 4).…”
mentioning
confidence: 95%
“…Reported values for the k cat and K m of RebH on L-tryptophan are 1.4 min −1 and 2.0 M, [13] respectively.…”
Section: Tablementioning
confidence: 99%
See 1 more Smart Citation